Respuesta :
Answer:
X=-2
Y=0
Step-by-step explanation:
X+y=-2 = x=-2-y
3x+4y=-6
3(-2-y)+4y=-6
-6-3y+4y=-6
y=0
x+3(0)=-2
x=-2
Answer:
[tex]\boxed {\boxed {\sf (-2,0)}}[/tex]
Step-by-step explanation:
To solve by substitution we must first isolate 1 variable in an equation.
Let's use the first equation.
[tex]x+3y= -2[/tex]
Subtract 3y from both sides to isolate the variable x.
[tex]x+3y-3y= -2 -3y[/tex]
[tex]x= -2 -3y[/tex]
Now we can substitute the expression (-2-3y) in for x in the second equation.
[tex]3x+4y= -6[/tex]
[tex]3(-2-3y)+4y= -6[/tex]
Distribute the 3. Multiply each term inside the parentheses by 3.
[tex](3*-2)+ (3*-3y)+4y=-6\\-6-9y+4y=-6[/tex]
Combine the like terms on the left side.
[tex]-6-5y= -6[/tex]
Add 6 to both sides to isolate the variable.
[tex]-6+6-5y=-6+6\\-5y=0[/tex]
Divide both sides by -5.
[tex]-5y/-5=0/-5 \\y=0[/tex]
Now we know that y is equal to 0 and can substitute it into the first equation and find x.
[tex]x+3(0)=-2[/tex]
[tex]x+0=-2 \\x= -2[/tex]
x is equal to -2 and y is equal to 0.